Off-Grid Connected Photovoltaic System for Rural Residential Electrification in Malaysia - Bolrahman, Lionel Jesson; Mohd Noor Abdullah (Evolution in Electrical and Electronic Engineering, 2022)
This project presents the design and system configurations for an off-grid connected photovoltaic (OGPV) system for rural residential electrification. The main difference between photovoltaic systems is in the type of sources available to supply electricity. Therefore, this project aims to design an OGPV system capable of providing reliable electricity supply in rural areas of Malaysia especially in Sabah and Sarawak. In order to achieve the objectives, there are a few comparisons from past projects in order to identify which case or method is the best to be used. The mathematical calculation is one of the methods in order to determine the relevant rate for each component involved in the off-grid PV system. PVsyst software is also used to design and simulate the system. The results from both mathematical calculation and PVsyst software simulation will be compared in order to ensure the results are synchronized. This proves that the result of the proposed design is suitable to be implemented with the exact rate of power load.